2013
DOI: 10.3233/jad-122308
|View full text |Cite
|
Sign up to set email alerts
|

Sex and ApoE Genotype Differences in Treatment Response to Two Doses of Intranasal Insulin in Adults with Mild Cognitive Impairment or Alzheimer's Disease

Abstract: A previous clinical trial demonstrated that four months of treatment with intranasal insulin improves cognition and function for patients with Alzheimer’s disease (AD) or mild cognitive impairment (MCI), but prior studies suggest that response to insulin treatment may differ by sex and ApoE ε4 carriage. Thus, responder analyses using repeated measures analysis of covariance were completed on the trial’s 104 participants with MCI or AD who received either placebo or 20 or 40 IU of insulin for 4 months, administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
152
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(164 citation statements)
references
References 43 publications
(58 reference statements)
8
152
1
3
Order By: Relevance
“…Preliminary clinical trials using intranasal insulin in patients with AD, but not diabetes, have shown some effectiveness on dementia symptoms (31), arguing that lack of insulin or insulin activity, rather than surplus insulin, may be a contributor to diabetes-associated AD. Subgroup analysis suggests that ApoE e4 carrier status increases the response to intranasal insulin, implying an insulin-cholesterol relationship in this patient population (32). Furthermore, we and others have shown that knockdown or inhibition of cholesterol synthesis from neurons creates insulin resistance in those cells (33,34), suggesting a feed-forward connection between diabetes and AD.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary clinical trials using intranasal insulin in patients with AD, but not diabetes, have shown some effectiveness on dementia symptoms (31), arguing that lack of insulin or insulin activity, rather than surplus insulin, may be a contributor to diabetes-associated AD. Subgroup analysis suggests that ApoE e4 carrier status increases the response to intranasal insulin, implying an insulin-cholesterol relationship in this patient population (32). Furthermore, we and others have shown that knockdown or inhibition of cholesterol synthesis from neurons creates insulin resistance in those cells (33,34), suggesting a feed-forward connection between diabetes and AD.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that a single dose of intranasal insulin acutely improved memory in memory-impaired older adults with AD or MCI and also improved memory and cognitive function with multiple treatments of patients with AD and MCI (23). Insulin was effective in improving performance on a verbal memory test in a group of AD and MCI patients; however, within these groups, patients who were APOEε4 positive or female showed poorer recall following insulin administration compared to patients who did not possess this allele or were male (25).…”
Section: Insulinmentioning
confidence: 93%
“…45,66 AD patients who were E4 carriers showed poorer responses to intranasal insulin treatment compared to AD patients who were E4 noncarriers. 55,67,68 This is a phenomenon observed not only with normal insulin, but also with the rapid-acting insulin, which has been shown to have enhanced effects on cognition in patients with AD. 69 It is interesting that whereas short-acting insulin was ineffective in E4 carriers, the longer acting insulin detemir produced cognitive improvements in E4 carriers, which was accompanied by an improvement in peripheral insulin resistance.…”
Section: Apoe and Insulin Interactionsmentioning
confidence: 99%